A study on model experiment and aerodynamic match of Wind Energy Fan (WEF). (August 2019) - Wang, Ziyun; Wu, Yuling; Lu, Siqiang; Meng, Xi; Zhang, Jigang
Highlights: A new ventilation method in the underground engineering is proposed. The Wind Energy Fan (WEF) has high-efficient utilization of wind energy. The influence rules of the peed increaser are revealed. A method is proposed to match the vertical wind turbine and the axial fan. Abstract: Wind energy is heavily utilized due to its clean renewability, large reserves and wide distribution. Wind energy is also the main driving force for natural ventilation, but it is very difficult to realize natural ventilation directly in the underground engineering. This study proposed an integrated device called Wind Energy Fan (WEF), which utilizes wind energy to drive the fan linked with the wind turbine directly by a transmission shaft, and this vertical wind turbine can realize the underground ventilation. An experiment platform was established to test the WEF performance with the consideration of three transmission ratios and two kinds of wind turbines with 3 and 5 blades. Results showed that the transmission ratio has a pronounced influence on the fan air volume and should be selected to obtain the rated air volume. The wind turbine with 3 blades is easier to start and its air volume is also 5.43%–17.85% more than that with 5 blades. According to the aerodynamic characteristic curves of the vertical wind turbine and axial fan, their matching method is proposed on the power and the speed. This scheme is an effective wind energy technology to realize the active utilization of wind energy in the underground engineering.